INTEGRATION OF SVM AND SMOTE-NC FOR CLASSIFICATION OF HEART FAILURE PATIENTS - Utari, Dina Tri (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
SMOTE (Synthetic Minority Over-sampling Technique) and SMOTE-NC (SMOTE for Nominal and Continuous features) are variations of the original SMOTE algorithm designed to handle imbalanced datasets with continuous and nominal features. The primary difference lies in their ability to generate synthetic examples for the minority class when dealing with continuous and nominal features. We employed a dataset comprising continuous and nominal features from heart failure patients. The distribution of patients' statuses, either deceased or alive, exhibited an imbalance. To address this, we executed a data balancing procedure using SMOTE-NC before conducting the classification analysis with SVM. It was found that the combination of SVM and SMOTE-NC methods gave better results than the SVM method, seen from the higher level of accuracy and F1 score. F1 gives less sensitivity to class imbalance compared to accuracy. Suppose there is a significant imbalance in the number of instances between classes. In that case, the F1 score can be a more informative metric for evaluating a classifier's performance, especially when the minority class is of interest.